Kritikan sosial filem Talentime (2009) / Umi Atikah Mohd Kamil - Umi Atikah, Mohd Kamil (2017)
Social criticism is an analysis that argues the positive and negative values in a certain work. Social criticism can be delivered in various methods, including academic writing, educational discourse, and mass media (Naila Mufidah, 2014). Besides that, social criticism is reviewed according to analytic process and detailed assessment. Therefore, the social criticism chosen for this thesis is the film Talentime, directed by Yasmin Ahmad. Talentime was released in 2009, where it remained as Yasmin Ahmad’s last contribution to Malaysian cinema. This thesis will utilize the sociology of literature theory by Ungku Maimunah Mohd. Tahir as the main framework. This thesis will only take one of the three principles of sociology of literature as outlined by Ungku Maimunah Mohd. Tahir, which is the sociology of literature as the societal overview (SSSGM). The objective of this study is to identify the social criticisms integrated in Talentime. The result of the analysis shows that there are two aspects of social criticisms that were highlighted in the film, which are racial integration and cultural integration. Based on observation, these two aspects are the most prominent that were successfully emphasized by Yasmin Ahmad.